2007
DOI: 10.1200/jco.2007.10.8076
|View full text |Cite
|
Sign up to set email alerts
|

Management of Borderline Ovarian Neoplasms

Abstract: Over the last decades, the management of borderline ovarian tumors (BOTs) has changed from radical surgery to more conservative therapy as a result of the need for fertility-sparing surgery and the increasing use of laparoscopy. The question is whether this is good clinical practice from an oncologic point of view. Here, recent literature regarding management of borderline ovarian neoplasms is reviewed, and oncologic concerns are discussed with emphasis on the mode of surgery and the possibility of fertility-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
155
2
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 48 publications
3
155
2
11
Order By: Relevance
“…For serous tumours, approximately 40% (range 28 -66%), and for mucinous tumours, about 8% (range 0 -13%) of the BOTs are observed to be bilateral Cadron et al, 2007;Kumpulainen et al, 2007). In this context, we observed that 19% of the clinical participants performed only unilateral ovarian cystectomy or at least USO.…”
Section: Surgical Therapymentioning
confidence: 85%
See 4 more Smart Citations
“…For serous tumours, approximately 40% (range 28 -66%), and for mucinous tumours, about 8% (range 0 -13%) of the BOTs are observed to be bilateral Cadron et al, 2007;Kumpulainen et al, 2007). In this context, we observed that 19% of the clinical participants performed only unilateral ovarian cystectomy or at least USO.…”
Section: Surgical Therapymentioning
confidence: 85%
“…Despite this fact, a removal of enlarged lymph nodes, so called 'bulky nodes', can be performed. In contrast to an ovarian carcinoma, invasion in the lymph nodes and metastatic spread of BOT are quite seldom and usually noninvasive (Hart, 2005;Cadron et al, 2007;Kumpulainen et al, 2007). Moreover, it is not yet clear whether these lymph node implantations represent real metastases, in situ transformed secondary muellerian epithelia or hyperplastic mesothelial cells (Shiraki et al, 1992;Chang et al, 2008).…”
Section: Surgical Therapymentioning
confidence: 99%
See 3 more Smart Citations